Estudo fitoquímico e avaliação das atividades antioxidante e anticolinesterásica de Tabernaemontana catharinensis - Nicola, Carla (My University, 2014)
Tabernaemontana catharinensis A.D.C. is a small tree of the Apocynaceae family currently found in Brazil, Argentina, Uruguay, Paraguay and Bolivia. The genus Tabernaemontana has evoke interest due the important biologic activity of their extracts, particularly, antimicrobial, anti-tumoral, antioxidant, anti-cholinesterasic and anti-inflammatory activities, most of which have been associated to indolic alkaloids. Although several biological activities of T. catharinensis extracts have been reported, few substances with both antioxidant and anticholinesterasic activities have been identified. The association of these properties may represent an alternative for the studies involving the control of neurodegenerative disorders as Alzheimer disease. In this context, the present work aimed to analyze the alkaloid content of the ethanolic extract of T. catharinensis and its fractions, as well as to evaluate their antioxidant and anticholinesterasic activities. The analyses of the ethanolic extract of T. catharinensis by mass spectrometry allowed identifying the presence of the alkaloids 16-epi-affinine, coronaridine-hydroxyindolenine, voachalotine, voacristine-hydroxyindolenine, and 12- methoxy-n-methyl-voachalotine, as well as an alkaloid with m/z 385.21 which spectrum suggest a derivative of voacristine or voacangine. The extract and its alkaloid rich fractions showed antioxidant activity, especially those that contain the alkaloid m/z385.21 or 16-epi-affinine with DPPH scavenging activity (IC50) between 37.18 and 74.69 μg/ml. Moreover, the extract and its fractions exhibited anticholinesterasic activity, particularly the fractions characterized by the presence of 12-methoxy-nmethyl- voachalotine, with IC50 = 2.1 e 2.5 μg/ml. Fractions with 16-epi-affinine combined good antioxidant (IC50= 65.59 to 74.69 μg/ml) and anticholinesterasic (IC50= 7.7 to 8.3 μg/ml) activities, representing an option for further studies aimed at treating neurodegenerative diseases.
Tabernaemontana catharinensis ADC é uma planta arbórea da família Apocynaceae encontrada no Brasil, Argentina, Uruguai, Paraguai e Bolívia. O gênero Tabernaemontana tem despertado interesse devido à importante atividade biológica dos seus extratos, particularmente, atividade antimicrobiana, antitumoral, antioxidante, anticolinesterásica, anti-inflamatória, entre outras, as quais têm sido associadas à presença de alcalóides indólicos. Embora diversas atividades biológicas tenham sido relatadas em extratos de T. catharinensis, poucas substâncias que combinem atividade antioxidante e anticolinesterásica têm sido descritas. A associação destas propriedades pode representar uma das alternativas para estudos visando o controle de desordens neurodegenerativas como a doença de Alzheimer. Neste contexto, o presente trabalho teve como objetivo analisar o conteúdo de alcalóides presentes em extrato etanólico e frações de T. catharinensis, assim com avaliar a sua atividade antioxidante e anticolinesterásica. A análise do extrato etanólico de T. catharinensis por espectrometria de massas permitiu identificar a presença dos alcalóides 16-epi-affinina, coronaridinahidroxiindolenina, voachalotina, voacristina-hidroxiindolenina e 12-metoxi-n-metilvoachalotina, além de um alcalóide com m/z 385,21 cujo espectro é compatível com derivado de voacristina ou voacangina. O extrato e suas frações ricas em alcalóides apresentaram atividade antioxidante, especialmente aquelas contendo o alcalóide com m/z 385,21 ou com 16-epi-affinina com capacidade de varredura de 50% do radical DPPH• da ordem de 37,18 a 74,69 μg/ml. Da mesma forma, tanto o extrato como as suas frações apresentaram atividade anticolinesterásica, sobressaindo as frações caracterizadas pela presença de 12-metoxi-n-metilvoachalotina, com IC50 de 2,1 e 2,5 μg/ml. Frações contendo 16-epi-affinina combinaram boa atividade antioxidante (IC50= 65,59 a 74,69μg/ml) e anticolinesterásica (IC50= 7,7 a 8,3 μg/ml), representando uma opção para futuras pesquisas envolvendo o tratamento de doenças neurodegenerativas.
Keywords: Apocinácea; Biotecnologia; Botânica